Consumption, Retirement and Life-cycle Prices: Evidence From Spain. - Sevilla-Sanz, A; Luengo-Prado, M (Department of Economics (University of Oxford), 2010)
Evidence from several countries reveals a substantial drop in household consumption around retirement age that some researchers believe is difficult to reconcile with standard life-cycle models. Using detailed expenditure data from a Spanish panel survey, we find no evidence of a consumption-retirement puzzle in Spain for the period of 1985-2004. However, we find a drop in food expenditure at home from 1998 to 2004 and evidence on households paying lower prices for the food they purchase after retirement in this latter period. Our findings are consistent with a household model that allows for home production whereby retirees substitute away from market goods to home production, as long as one accounts for the greater participation in housework by men after retirement coinciding with the latter period of the survey.